Spectrum of adrenal lesions on fine needle aspiration cytology - Chanchal Rana; Narendra Krishnani; Niraj Kumari (Wolters Kluwer Medknow Publications, 2012)
Background: Fine needle aspiration (FNA) cytology of adrenal gland is not a commonly performed technique and is limited primarily to tertiary care centers. However, it is a sensitive and specific procedure in the workup of patients with adrenal gland's mass lesions. Though cytomorphological features for various lesions have been described, there are a limited number of studies in cytologic literature. Aims: We report our 7 years of experience in FNAC of adrenal lesions. We have not only described the cytomorphological details of different lesions, but also tried to discuss the various diagnostic difficulties encountered during reporting of adrenal fine needle aspirations. Materials and Methods: All ultrasound-guided percutaneous aspirations of adrenal gland received in the department between the years 2002 and 2009 were reviewed. There were a total of 52 FNA samples of adrenal masses from 35 patients in 7 years. The lesions were categorized as non-neoplastic and neoplastic categories. Neoplastic lesions were further divided into benign and malignant lesions. Results: In our study, FNA proved to be 100% specific for diagnosing malignant lesions. The overall inadequacy rate was 11.4% with no major complications of the procedure. A wide variety of non-neoplastic as well as neoplastic lesions were identified.